2020
DOI: 10.3389/fimmu.2020.01372
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Induced Transmembrane Protein (IFITM3) Is Upregulated Explicitly in SARS-CoV-2 Infected Lung Epithelial Cells

Abstract: Current guidelines for COVID-19 management recommend the utilization of various repurposed drugs. Despite ongoing research toward the development of a vaccine against SARS-CoV-2, such a vaccine will not be available in time to contribute to the containment of the ongoing pandemic. Therefore, there is an urgent need to develop a framework for the rapid identification of novel targets for diagnostic and therapeutic interventions. We analyzed publicly available transcriptomic datasets of SARS-CoV infected humans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 38 publications
1
75
0
Order By: Relevance
“…Given SARS-CoV-2 infection of barrier cells, we thus wondered whether astrocytes would exhibit similar hallmarks of inflammation with concomitant consequences for neuronal health. We indeed observed hallmarks of astrogliosis 87 and viral defense 50 in upregulated GFAP and IFITM3 expression, as well as neurotoxicity in the secreted factor CHI3L1 8890 (Fig. 3b, Fig.…”
Section: Potential Synaptic Dysfunction Specifically In Layer 2/3 Excmentioning
confidence: 56%
See 1 more Smart Citation
“…Given SARS-CoV-2 infection of barrier cells, we thus wondered whether astrocytes would exhibit similar hallmarks of inflammation with concomitant consequences for neuronal health. We indeed observed hallmarks of astrogliosis 87 and viral defense 50 in upregulated GFAP and IFITM3 expression, as well as neurotoxicity in the secreted factor CHI3L1 8890 (Fig. 3b, Fig.…”
Section: Potential Synaptic Dysfunction Specifically In Layer 2/3 Excmentioning
confidence: 56%
“…3b). IFITM3 serves as the first line of defense against viral infection 49 and its upregulation is a marker of SARS-CoV-2 infection across publicly available datasets 50 . We also observed in the cortex parenchyma a consistent upregulation of the newly described viral entry receptor NRP1 41,51,52 (Fig.…”
Section: Sars-cov-2 Accumulation In Barrier Cells Stimulates Inflammamentioning
confidence: 99%
“…This may be due to association with the activation of the cytokine storm in infected patients during immune response (Gao et al, 2020;Huang et al, 2020;Ruan et al, 2020). Nevertheless, Hachim et al (2020) also reported an early upregulation of IFITM3 in SARS-CoV-2 infected patients. Taken together, the roles in the infection played by these commonly expressed genes at a critical site -possibly the entry route of viral-host interaction in the nasopharynx raises the possibility of low invasive tests to investigate these genes in peripheral blood and support personalized medicine.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, the soluble levels of IFN-I were not addressed, but a possible counterbalance played by upregulation of anti-inflammatory signalling by IL-10 could be in line to what was observed by Blanco-Melo and colleagues (2020). Hachim et al (2020) also reported that genes, especially the IFITM3 gene, involved in IFN response to a viral infection such as type 1 interferon signalling pathway, were upregulated in SARS-CoV-2 infected lung epithelial cells. This further elucidates the release of IFN by the innate immune system in response to viral RNAs, such as is the case with SARS-CoV-2 (Nelemans & Kikkert, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…We used GEOquery and limma R packages through the GEO2R tool for each dataset (22). We selected the differentially expressed probes, as previously described (23). Briefly, we sorted the genes related to the filtered probes according to the False Discovery Rate (FDR) and selected the top 2,000 differentially expressed probes with FDR <0.05 from each dataset.…”
Section: Degsmentioning
confidence: 99%